STABILITY ANALYSIS OF EDGE RIVER LAWE LIANG PANGI AT LEUSER SUB-DISTRICT, SOUTHEAST ACEH REGENCY TOWARDS FLASH FLOOD - Azmeri Azmeri; Devi Sundary (Inersia: Jurnal Teknik Sipil, 2019)
Flash flood is a process flow of heavy water and massive load concentrated is accompanied, also rock chunks, soil and logs (debris) from the upstream. Flash flood’s triggered by climatology and geological factors, landslides and natural damming at the upstream. The rising of water discharge flood process occurs suddenly and rapidly. The research in the Lawe Liang Pangi Watershed, Leuser Sub-district, Southeast Aceh Regency. Based on information, there are heavy rains occurred during the 3 days before the flood. Flooding occurred on Friday evening, August 17, 2012 at 22:00. Occured landslide at 15 locations. The most substantial damage is Naga Timbul, Suka Damae, Sepakat, Gaya Sendah, Punce Nali, and Bun-bun Indah villages. Liang Lawe Pangi watershed topography is mountainous, moderate to steep slope. The soil type is a little fine sandy silt loam and dark brown, and the soil type is erosion susceptible. The river bank stability test results for the two sampling locations, the safety factor in extreme conditions (flooding) is smaller (1,34) than the standard value (1,50). The flood conditions (inundation) is not secure against river bank scour. It is certainly more dangerous when taken by flash floods at a large velocity and followed by massive load. Recommendations for prevention and  mitigation of flash flood disasters in Leuser Sub-district, the disaster prevention and mitigation in the structural measures that to typical flood prone locations and non-structural measures including vegetation and public education work for the land management.